A Method for determining anisotropic transport properties in fuell cell porous transport layers - D. Hamilton (Canadian Institute of Mining, Metallurgy and Petroleum, 2005)
The electrode of a PEM fuel cell consists of two distinct sections - the catalyst layer and the porous transport layer (PTL). There are several kinds of PTL material, although all use carbon fibres as the solid fraction. The fibres can be matted to form a paper, woven into a cloth, or chopped to form a felt. Despite the different morphologies of the media, they are all anisotropic in structure, that is the majority of continuous fibres lie perpendicular to the direction of bulk transport. Currently, no models account for anisotropy and all transport coefficients are calculated as volume weighted averages or from empirical correlations (not developed for fibrous porous media). The present work presents a new methodology for determining anisotropic transport coefficients in fibrous porous media. A numerical experimentation process is employed wherein random samples of the PTL are generated and used to solve a diffusion transport equation. Effective transport coefficients are determined by integration of flux across the domain boundaries once a steady state solution has been reached. Multiple random samples at each porosity are generated in order to predict statistical variance. The results are correlated for ease of implementation in full PEM models.